Effect of torrefaction temperature on properties of Patula pine - Sergio Ramos-Carmona; Juan F. Pérez; Manuel Raúl Pelaez-Samaniego; Rolando Barrera; Manuel Garcia-Perez (Maderas: Ciencia y Tecnología, 2017)
The objective of this work was to study the effect of torrefaction temperature on properties of patula pine (Pinus patula) wood that could be of interest for further thermochemical processing. Torrefaction temperature was varied from 200 to 300 °C for 30 minutes using a batch spoon type reactor. Raw and torrefied materials were characterized for proximate and ultimate analyses, thermogravimetry, and pyrolysis gas chromatography/mass spectrometry (Py-GC/MS). Results showed that torrefied pine has greater higher heating value and chemical exergy due to the reduction of O/C and H/C ratios. Compared with raw biomass, the material torrefied at 200 and 250 °C did not present significant changes  in chemical composition and thermal behavior. Conversely, material torrefied at 300 °C did show important changes in both chemical composition and thermal behavior. Py-GC/MS results suggested that the main constituents of biomass, i.e., hemicellulose, cellulose and lignin, suffer a progressive thermal degradation with increase in torrefaction temperature.